Effectiveness of Debugging-Design in 2D Simulations to Facilitate STEAM Learning - Tembo, Tercia Marie Tafadzwa; Lee, Chien Sing * (Asia-Pacific Society for Computers in Education, 2018)
In our previous paper we discussed reports of the declining interest in STEM subjects of high school students in Malaysia and proposed a framework and methodology that uses 2D simulation application to facilitate learning physics in STEAM. In this small pilot case study, we present our hypothesis using a debugging-design approach with 2D simulation applications and the development of scaffolds and gamification for the learning environment. A preliminary experiment was conducted with middle school students to test the system’s effectiveness. We present a breakdown of the student assessments and analyze the questionnaire responses. Findings indicate that although the system needs a bit more work on scaffolding features, it is effective in helping students increase their interest in STEAM and move up Bloom’s Taxonomy.